2017
DOI: 10.1063/1.4973549
|View full text |Cite
|
Sign up to set email alerts
|

Is sodium a superconductor under high pressure?

Abstract: Superconductivity has been predicted or measured for most alkali metals under high pressure, but the computed critical temperature (T) of sodium (Na) at the face-centered cubic (fcc) phase is vanishingly low. Here we report a thorough, first-principles investigation of superconductivity in Na under pressures up to 260 GPa, where the metal-to-insulator transition occurs. Linear-response calculations and density functional perturbation theory were employed to evaluate phonon distributions and the electron-phonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Remarkably, as first predicted by theory [88], sodium undergoes a metal to insulator (MIT) transition by 200 GPa, which results from the overlap of core electrons and the concomitant localization of p − d hybridized valence electrons, which render this phase an electride [61]. Theoretical calculations have found that the maximum electron-phonon-coupling parameter, λ, for sodium occurs for the cI16 phase near 140 GPa [89]. Estimates of the T c within the Allen-Dynes modified McMillan equation and µ * = 0.13 found a maximum T c of 1.2 K, leading to the conclusion that superconductivity in sodium prior to the MIT is weak or non-existent.…”
Section: Electronic Structure and Superconductivity Under Pressurementioning
confidence: 70%
“…Remarkably, as first predicted by theory [88], sodium undergoes a metal to insulator (MIT) transition by 200 GPa, which results from the overlap of core electrons and the concomitant localization of p − d hybridized valence electrons, which render this phase an electride [61]. Theoretical calculations have found that the maximum electron-phonon-coupling parameter, λ, for sodium occurs for the cI16 phase near 140 GPa [89]. Estimates of the T c within the Allen-Dynes modified McMillan equation and µ * = 0.13 found a maximum T c of 1.2 K, leading to the conclusion that superconductivity in sodium prior to the MIT is weak or non-existent.…”
Section: Electronic Structure and Superconductivity Under Pressurementioning
confidence: 70%